Shopping center e a (re) produção do espaço em Santarém - PA - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The production of urban space through shopping centers is increasingly evident in cities, which through these developments and the state contribute to an increasingly unequal and fragmented urban space. The aim of this paper is to analyze the relationship between the Rio Tapajós shopping center and the production of urban space in Santarém, with an emphasis on the Elcione Barbalho neighborhood and the Vista Alegre do Juá occupation, which are studied here in particular. After its insertion in 2014 in the Elcione Barbalho neighborhood, on the west side of the city, it led to a series of transformations in its surroundings. This study sought to analyze the transformations resulting from the insertion of the shopping mall and how, through it, it contributed to an increase in value, specifically in the Elcione Barbalho neighborhood and the Vista Alegre do Juá Occupation. The methodology adopted is based on bibliographical research involving the theme of Urban Geography; fieldwork was also carried out at Rio Tapajós Shopping, in the Elcione Barbalho neighborhood and in the Vista Alegre of the Juá Occupation, where forms were applied to characterize the users of the shopping mall; for the residents of the neighborhoods studied to verify real estate and commerce in the areas. At the end of these stages, the results were that the shopping center has a very large reach in the city, as verified by the transportation, the frequency and the activities such as leisure and entertainment and other attractions for this enterprise. It was also found that in the Elcione Barbalho neighborhood and in the Vista Alegre do Juá occupation there have been urban interventions carried out by the state that have increased the value of these areas. Finally, this study concludes that Rio Tapajós Shopping has proved to be a very significant driver of changes in Santarem's urban space, in which it is contributing to a notorious expansion to the west of the city, due to the significant changes in the vicinity of this commercial development.
Shopping Center and the (re) production of Urban Space in Santarém - PA
Keywords: Crescimento urbano - Santarém (PA); Santarém (PA) - Geografia; Urbanização; CIENCIAS HUMANAS; Espaço urbano; Elcione Barbalho; Ocupação Vista Alegre do Juá; Santarém; Rio Tapajós Shopping